STUDY OF FINANCIAL REPORTING AND AUDIT QUALITY USING VOSVIEWER - Cristino Gusmao; Ericke Fridatien; Adolmando S. Amaral; Witjaksono Eko Hartoto; Aprih Santoso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to analyze the research map related to Audit Quality using the Vosviewer bibliometric study. The methods employed to analyze the data in this study include using the Google Scholar tool Publish or Perish to look for papers that contain the term Audit Quality over a ten-year period starting in 2014 and ending in 2024, sorting the metadata of articles that meet the study criteria with Mendeley, and finally mapping the findings of the VOSViewer bibliometric visualization related to Audit Quality by grouping them according to the number of clusters and items. The study's findings demonstrate the vast amount of literature on audit quality, which is categorized into three clusters and encompasses fifty topic items. This study's involvement and purpose illustrate the key findings of audit quality research. Future scholars can use the visualization's findings as a guide to do additional research.